2005
DOI: 10.1007/s10620-005-2762-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of ABO Blood Group, Age, Gender, Smoking, and Helicobacter pylori Infection

Abstract: It is well known that blood group antigens are related to the development of peptic ulcer and gastric carcinoma. This study sought to determine the relationship between H. pylori and ABO/Rhesus blood groups, age, gender, and smoking. Patients (335 women and 205 men; mean age, 51.68 +/- 15.0 years; range, 18-85 years) who attended our outpatient clinic were enrolled in the study. All patients were randomly selected in each age group. Demographic data recorded for each patient included age, gender, and tobacco u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
61
11
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 25 publications
12
61
11
4
Order By: Relevance
“…Helicobacter pylori infection is the most common chronic bacterial infection around the world (Kanbay et al, 2005). It has been shown that 50% adult in developed countries and 90% adults in developing countries were positive of serum antibodies against H. pylori (Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Helicobacter pylori infection is the most common chronic bacterial infection around the world (Kanbay et al, 2005). It has been shown that 50% adult in developed countries and 90% adults in developing countries were positive of serum antibodies against H. pylori (Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have discovered a blood group antigen binding adhesin (BabA), which help the organism to adhere to the epithelial cells (Martins et al, 2006). Boren et al demonstrated that, the H and Leb antigens of the ABH and Lewis (Le) blood group systems are the receptors on gastric epithelial cells for H pylori (Kanbay et al, 2005). It has been shown that gastric mucosa of blood group O are more prone for the attachment of H pylori, because they had more receptors, and Lewisb antigens mediated the attachment of H. pylori to the mucosa (Kanbay et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations